2014
DOI: 10.1089/hum.2014.011
|View full text |Cite
|
Sign up to set email alerts
|

Translational Fidelity of Intrathecal Delivery of Self-Complementary AAV9–Survival Motor Neuron 1 for Spinal Muscular Atrophy

Abstract: Spinal muscular atrophy (SMA) is a neuromuscular disease caused by mutations in survival motor neuron 1 (SMN1). Previously, we showed that central nervous system (CNS) delivery of an adeno-associated viral (AAV) vector encoding SMN1 produced significant improvements in survival in a mouse model of SMA. Here, we performed a dose-response study in SMA mice to determine the levels of SMN in the spinal cord necessary for efficacy, and measured the efficiency of motor neuron transduction in the spinal cord after in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 42 publications
3
78
0
2
Order By: Relevance
“…Although initial indications from these studies are encouraging, it is evident that second-generation vectors that exhibit a greater safety profile and transduction activity may be required before this optimism can be fully realized (Cheng, 2014). Several recent studies have suggested that some AAV serotypes could achieve extensive CNS distribution in non-human primates (Passini et al, 2014;Yang et al, 2014a). However, the optimal serotype, route of delivery and brain distribution to critical brain regions must be further investigated prior to the development of glucocerebrosidase gene therapy for conditions requiring widespread distribution of therapeutic proteins in the CNS, including lysosomal storage diseases and Gaucher-related PD.…”
Section: Glucocerebrosidase Augmentation Via Gene Deliverymentioning
confidence: 99%
“…Although initial indications from these studies are encouraging, it is evident that second-generation vectors that exhibit a greater safety profile and transduction activity may be required before this optimism can be fully realized (Cheng, 2014). Several recent studies have suggested that some AAV serotypes could achieve extensive CNS distribution in non-human primates (Passini et al, 2014;Yang et al, 2014a). However, the optimal serotype, route of delivery and brain distribution to critical brain regions must be further investigated prior to the development of glucocerebrosidase gene therapy for conditions requiring widespread distribution of therapeutic proteins in the CNS, including lysosomal storage diseases and Gaucher-related PD.…”
Section: Glucocerebrosidase Augmentation Via Gene Deliverymentioning
confidence: 99%
“…Several studies quantified transduction levels and patterns in brain and spinal cord of mice after CSF and IV delivery of AAV [24][25][26][27][28][29] . The use of different injection strategies, AAV serotypes, as well as dosing led to variable results in pigs and nonhuman primates 21,24,[30][31][32][33][34] .…”
Section: Introductionmentioning
confidence: 99%
“…Contemporary studies confirmed the benefits of intravenous scAAV9-SMN1 delivery in P1 SMA mice, and also demonstrated remarkable protection following CNS and intramuscular delivery [5][6][7]. Importantly, the therapeutic relevance of this approach has been demonstrated by successful systemic or intrathecal delivery of viral vectors carrying a green fluorescent protein into juvenile pigs and primates, resulting in robust expression [4,8,9]. Indeed, intrathecal delivery of scAAV9 carrying human SMN1 conferred significant benefit to a pig model of SMA [10].…”
mentioning
confidence: 88%